2022
DOI: 10.1186/s12911-022-01785-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of continuous care model using a smartphone application on adherence to treatment and self-efficacy among patients with multiple sclerosis

Abstract: Background Adherence to disease-modifying therapy is important in patients with Multiple Sclerosis (MS) to increase the positive outcomes and improve the quality of life. This study aimed to determine the effects of Continuous Care Model (CCM) using a smartphone application on adherence to treatment and self-efficacy among MS patients. Methods This quasi-experimental study with pre/posttest design was conducted on 72 MS patients in Shiraz, Iran fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…The possible total score of the scale is 11–66 23 . Another study also showed that the Persian version of this scale had acceptable validity and reliability ( α = 0.92) 24 …”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…The possible total score of the scale is 11–66 23 . Another study also showed that the Persian version of this scale had acceptable validity and reliability ( α = 0.92) 24 …”
Section: Methodsmentioning
confidence: 91%
“…23 Another study also showed that the Persian version of this scale had acceptable validity and reliability (α = 0.92). 24 27 This inventory has acceptable validity and reliability. 28…”
Section: Msss Is a Valid And Reliable Scale Developed By Rigby Et Al ...mentioning
confidence: 95%
“…Camara et al [ 36 ] reported that receiving information about the disease, contacting the doctor more often, and not missing check-up visits contribute to treatment adherence. Adequate care, education, and a specific program, i.e., Continuous Care Model (CCM) using a smartphone application, are the factors responsible for high adherence among patients with MS [ 38 , 39 ]. In our study, patients with a higher QOL in the RHCS domain (more satisfied with the healthcare system) adhered more to the treatment recommendation.…”
Section: Discussionmentioning
confidence: 99%
“…Smartphone apps offer certain advantages to improve treatment adherence and treatment effectiveness by providing patients with a highly convenient way to access treatment materials and complete at-home assignments independently (Cavanagh et al, 2020). Specifically, research has found that smartphone apps have been effective in helping patients make positive behavioral changes such as adhering to specific medical treatment regimens, making healthy lifestyle choices, and increasing self-efficacy (Lunde et al, 2018;Kazemi et al, 2022). To address sleep difficulties among MHS beneficiaries, the Veteran's Affairs (VA), Stanford University, and Department of Defense (DOD) developed CBTi Coach to support patient adherence to clinical treatment by utilizing features such as a sleep diary tracker, reminders, and checklists (Koffel et al, 2018).…”
Section: Introductionmentioning
confidence: 99%